Pertanian Organik sebagai Alternatif Teknologi Agrowisata di Sembalun Lawang - Tomi Cahyadi Utama; Dewi Yuliantika; Putri Dinda Gunawan; Handika Setiawan; Lale Girvina Ratu Anindy; Neng Annisa Is Amalia; Muhammad Wahyu; Suryati Suryati; Muhammad Zidane Bachtiar; Muhammad Sarjan (Pascasarjana Universitas Mataram, 2022)
Indonesia is an agrarian country with a tropical climate and has abundant resource potential in the form of various agricultural commodities. Sembalun lawang is one of the villages located in Sembalun District with a population in 2021 of 4,985 people, where most of the population has a livelihood as farmers. One of the attractions of Sembalun Lawang Village for tourists lies in the agricultural sector, so agrotourism in this area must be improved. The implementation methods used are observation, experimental, and socialization. Observations made in Sembalun Lawang Village showed that the majority of farmers still did not apply organic farming in farming and depended on the use of chemicals, so thematic KKN students conducted experiments to test the growth of pakcoy plants that had been given liquid organic fertilizer treatment. Socialization is carried out to the community to educate about the dangers of using synthetic chemicals and introduce organic farming that is more environmentally friendly